STUDI KUALITAS PERAIRAN TELUK EKAS BERDASARKAN KOMPONEN FISIKA-KIMIA PADA BULAN MARET 2014 - Muhammad Ramdhan (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2015)
The research was conducted on 9 to 15 March 2014 in the Ekas Bay region, East Lombok, West Nusa Tenggara Province. Water quality data acquisitions was done with purposive sampling by using a multiparameter WQC-24 TOA-DKK, floating drought in situ current measurement and water sampling for laboratory check. The parameters measured are temperature, salinity, DO, dT, pH, flow speed, Turbidity, TOM, NO2, NH3, PO4P, Chlorophyll and TSS. Data analysis using descriptive and Biplot graph analysis. The results showed range of values ​​for all parameters was almost in accordance with KepmennegLH No. 51 of 2004, based on physico-chemical parameters measured, still in good condition. Only the phosphate values ​​which average value of 0.41 mg / L is above the standard of Kepmenneg LH No. 51 of 2004 which is 0.015 mg / L. Permalink/DOI: http://dx.doi.org/10.15408/sd.v2i1.1378